Mapping disaster hazards and risks – a case study in Kuala Lumpur City (KLC) - Zul Bahari, Ahmad Najman ‘Azam; Ng, Choy Peng; Wong, Mohd Muhaimin Ridwan; Mohd Rofi, Muhamad Faisharulfaizi; Ahmad, Nordila; Abas, Fuad; Law, Teik Hua (National University of Malaysia, 2025)
Kuala Lumpur, the capital city of Malaysia, is vulnerable to various natural and man-made disasters. Kuala Lumpur City (KLC) encounters distinctive difficulties in managing urban disasters, mainly because of its dense population, critical infrastructure, and economic importance. Mapping the hazards and risks of disasters in KLC is crucial for enhancing its resilience against disasters and ensuring the effectiveness of emergency response, humanitarian aid, and disaster relief efforts. The objective of this study is to develop a comprehensive master plan for the management of disasters in KLC. The plan will serve as the initial phase in the civil-military coordinating response architecture for humanitarian aid and disaster relief (HADR). The approach entails creating a hazard map delineating regions susceptible to flash floods and landslides, frequently occurring in KLC. In addition, a vulnerability map was generated to evaluate the region’s proneness to disasters and identify safe areas within KLC. Additionally, road vulnerability assessments were performed to determine the most direct route for HADR activities. Furthermore, a customised disaster risk map was created exclusively for the KLC. This work contributes to the growing body of literature on urban disaster management, offering valuable insights for other metropolitan areas facing similar challenges.